SOME ASPECTS OF FISHERY AND BIOLOGY OF SARDINES . OF WALTAIR AREA - Rao, T Appa (Indian Journal of Fisheries, 2011)
Along the Waltair Coast the fishing season for Sardinella fimbriata startsin October-November and terminates in May-June, whereas for Sardinella gibbosathe fishing season is shorter, March to Juiie-July. The average annual landings ofboth the species together are 73 t. S. fimbriata measuring less than 120 mm domi- 'nates the esriier part of the season and larger specimens measuring more than120 mm dominate the later part. The reverse is the case for 5. gibbosa. Both thesardines feed on planktonic copepods, diatoms and larvae of other organisms.Length-weight relationship, sex ratio and fecundity hajve been studied.